EFEKTIVITAS MODEL PEMBELAJARAN CHANGE OF PAIRS BERBASIS PENDIDIKAN KARAKTER TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS MATERI LOGIKA MATEMATIKA KELAS XI - Puput Fitriyadi; Dwi Sulistyaningsih; Martyana Prihaswati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
This research to determine the effectiveness of the application of learning model of Change of Pairs Based on Character Education. This research is an experimental research. The sampling technique used Purposive Sampling technique. Data analysis techniques used are the test of completeness, influence test, and test the average difference. The results of this study indicate that: (1)The ability to understand the concept of achieving KKM with an average value of 84.6429 and the percentage of completeness is 82.1429%. (2)There is influence of motivation and honesty to ability understanding of concept equal to 81%. (3) There is an average difference between the experimental class and the control class with an average rating of 84.6429 and 70.0729. So it can be concluded that the application of Change of Pairs learning model based on character education on the ability to comprehend the concept of mathematical material of effective logic. Keywords: Change of Pairs, Character Education, Understanding concept